Virtual Planning for Dental Implant Placement Using Guided Surgery - Viegas, Vinicius Nery; Lacroix, Celso Gustavo Schwalm; Pagnoncelli, Rogério Miranda; Oliveira, Marília Gerhardt de (IntechOpen, 2011)
None